Case Report: Clinical metastasis characteristics of lung adenosquamous carcinoma with ROS1 rearrangement - Chen, Xi; Ma, Kewei; Ma, Xiaobo; Zhu, Wenhao; Liu, Bo; Duan, Xiumei; Xu, Yinghui (Frontiers in Medicine, 2025)
Adenosquamous carcinoma (ASC) of the lung is a rare and aggressive subtype of non-small-cell lung cancer, with a poor prognosis. Previous studies have revealed the existence of numerous oncogenic mutations shared between the adeno and squamous components, thereby implying a potential link between these two pathologies. Nevertheless, the genetic origin and underlying mechanisms of such a connection remain subjects of controversy. Here, we present a remarkable case of ASC where the primary tumor and mediastinal lymph node (LN) metastasis were adenosquamous, while the hilar LN metastasis was pure squamous cell carcinoma. Remarkably, a ROS1 rearrangement was identified in all lesions, strongly suggesting a common origin for the adeno-squamous components. In other words, ASC represents an intermediate state during the potential transformation from AC to SCC. Through whole-exome sequencing and immunohistochemistry, we analyzed the tumor immune microenvironment and the expression of key lineage-defining transcription factors, including NKX2-1, FOXA2, and SOX2. Our findings suggest these factors contribute significantly to the adeno-to-squamous pathological transformation. This exceptional case offers valuable insights that could potentially aid in the future recognition and treatment of ASC.